FRAUD RISK IN TIMES OF CRISIS AND THE DEVELOPMENT OF ITS MITIGATION TOOLS - Agnieszka Skoczylas-Tworek (Polityki Europejskie, Finanse i Marketing)
The phenomenon of fraud has accompanied organizations since their beginnings. Its scale and frequency of occurrence are changing with the economic, legal and economic situation in the domestic and international markets. The factors conducive to its escalation are crisis situations, the determinants of which are to be found in both external and internal factors. Hence, in order to reduce the probability of occurrence and the effects of the impact of fraud risk on the organization, it is necessary to take appropriate measures and implement control mechanisms. The purpose of the publication is to analyze the development of anti-fraud controls diagnosed on the basis of periodic studies of the phenomenon of fraud and conducted by the ACFE organization between 2006-2022 and to assess the degree of their application in Polish business entities. The basic research method was quantitative and qualitative analysis. The analyses carried out showed that entities use anti-fraud controls. However, the prevalence of their application is progressing in accordance with the implementation of legal regulations and guidelines in this area. This means that state and international organizations’ activities significantly impact the development of anti-fraud controls.